2016
DOI: 10.3329/jbsp.v11i2.30648
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and visual reaction time and peripheral field of vision in helmet users

Abstract: Background: The incidence of fatal accidents are more in two wheeler drivers compared to four wheeler drivers. Head injury is of serious concern when recovery and prognosis of the patients are warranted, helmets are being used for safety purposes by moped, scooters and motorcycle drivers. Although, helmets are designed with cushioning effect to prevent head injuries but there are evidences of increase risk of neck injuries and reduced peripheral vision and hearing in helmet users. A complete full coverage helm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Another similar study by Abbupillai et al . [ 5 ] found that the VRT was not affected in any healthy female and male helmet users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another similar study by Abbupillai et al . [ 5 ] found that the VRT was not affected in any healthy female and male helmet users.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] The field of view and use of helmets have received fair attention in the scientific literature. [ 5 ] McKnight et al [ 6 ] analyzed data for the actual causes of road accidents and concluded that 11% of the accidents were related to the rider's field of view. In recent times, Joshi et al .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a common reason behind helmet non-use is a limited visual field, which certainly presents a problem because peripheral vision is an essential factor for safety in alpine skiing [10,11]. Advanced visual reaction time, visual memory, and visual discrimination are directly translated to improved sport performance and reduced locomotor injury risk [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, common arguments for helmet non-use are impaired hearing and impaired vision [ 13 , 14 , 15 , 16 ]. In addition, it has been suggested that a helmet might alter skiers’ ability to sense the surroundings, potentially leading to dangerous situations.…”
Section: Introductionmentioning
confidence: 99%